Knowledge and Practices of Mask Usage During the COVID-19 Pandemic - Amorim, M. Francisca; Nunes Sousa, João; Fróis, Ana Teresa; Rodrigues Pacheco, Diana (Gazeta Médica, 2022)
INTRODUCTION: The use of a facemask is universally recommended to prevent the transmission of COVID-19, but errors of usage are frequently observed. We aimed to evaluate knowledge and practices of facemask usage, to determine the need for health education strategies. MATERIAL AND METHODS: Analytical cross-sectional study with a self-administered questionnaire, applied to a convenience sample of adult patients of three primary health care units. RESULTS: 299 valid questionnaires were obtained, with a sample composed mainly of the feminine gender (71.6%) and an average age of 45.0±15.1 years. The type of facemask identified as most used was the surgical mask (82.4%), with efficacy of protection as the main reason for the choice (53.6%). Those who perceived a higher risk of being infected opted for a facemask with greater efficacy (54.6% vs 26.5%; p=0.046), while those who felt no need to use a facemask decided based on availability (50.0% vs 22.2%; p=0.025). Those who considered the mask necessary displayed less usage errors (p<0.001) and a higher rate of hand disinfection (82.3% vs 23.5%, p<0.001). There were no cases of facemask usage without errors. DISCUSSION: Around 98% of people referred using the facemask all or most of the times they left the house, complying with current recommendations. Those who were not vaccinated perceived a higher risk of being infected, which reveals an overall trust in the vaccine. CONCLUSION: Population knowledge regarding facemasks and their aim potentiates their efficacy and correct usage.